2019
DOI: 10.1002/ece3.4921
|View full text |Cite
|
Sign up to set email alerts
|

Data partitioning and correction for ascertainment bias reduce the uncertainty of placental mammal divergence times inferred from the morphological clock

Abstract: Bayesian estimates of divergence times based on the molecular clock yield uncertainty of parameter estimates measured by the width of posterior distributions of node ages. For the relaxed molecular clock, previous works have reported that some of the uncertainty inherent to the variation of rates among lineages may be reduced by partitioning data. Here we test this effect for the purely morphological clock, using placental mammals as a case study. We applied the uncorrelated lognormal relaxed clock to morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…Unlike the Explosive and Long Fuse Models , both of which are widely advocated in the literature, support for the Short Fuse Model is restricted to a relatively small number of studies. These include early molecular clock analyses (e.g., Kumar and Hedges, 1998), a supertree analysis (Bininda-Emonds et al, 2007), and more recently morphological clock studies (Puttick et al, 2016; Caldas and Schrago, 2019). The most explicit support for the Short Fuse Model comes from Bininda-Emonds et al (2007), who used a matrix representation with parsimony approach to build a supertree representing ∼99% of mammalian species-level diversity.…”
Section: Review and Comparison Of Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the Explosive and Long Fuse Models , both of which are widely advocated in the literature, support for the Short Fuse Model is restricted to a relatively small number of studies. These include early molecular clock analyses (e.g., Kumar and Hedges, 1998), a supertree analysis (Bininda-Emonds et al, 2007), and more recently morphological clock studies (Puttick et al, 2016; Caldas and Schrago, 2019). The most explicit support for the Short Fuse Model comes from Bininda-Emonds et al (2007), who used a matrix representation with parsimony approach to build a supertree representing ∼99% of mammalian species-level diversity.…”
Section: Review and Comparison Of Modelsmentioning
confidence: 99%
“…These authors recommended that the results of such analyses be treated with caution. Caldas and Schrago (2019) compared the results of molecular and morphological clocks with internal node calibrations and found that the majority of estimated ages were older with the morphological clock than the molecular clock. However, Caldas and Schrago (2019) estimated interordinal ages based on the morphological clock are younger than Puttick et al (2016) estimated ages based on the morphological clock with tip dating.…”
Section: Node Dating and Beyondmentioning
confidence: 99%
“…While some investigators have compared dates from morphological and molecular data, they have generally used multiple calibrations in their analyses [e.g., 1,5,8]. Overall, they found that both data sources resulted in comparable time estimates, except for some morphological estimates that were older than molecular, depending on the choice of calibration priors and data partitioning.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the time estimates obtained from molecules and morphology is possibly because morphological matrices generally consist only of characters that vary among terminals; thus, the rate of morphological change, which ultimately impacts divergence time estimation, may be biased. Furthermore, it is generally accepted that phenotypic diagnostic changes of lineages will accumulate after their complete genetic isolation [27] while genetic changes may start well before the speciation time [8,28,29]. Therefore, the relative pace of the morphological clock should be slower than the molecular clock and thereby morphological time estimates could become younger than molecular time estimates.…”
Section: Analyses Without Internal Calibrationsmentioning
confidence: 99%
See 1 more Smart Citation